2021
DOI: 10.12669/pjms.38.1.4531
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of computer aided reading of chest x-ray in screening for pulmonary tuberculosis in comparison with Gene-Xpert

Abstract: Background & Objectives: Pakistan ranked fifth amongst 22 high-burden Tuberculosis countries, and it is  an epidemic in Pakistan, hence screening is performed nationally, as part of the ambitious ZERO TB drive. Our objective was to assess the diagnostic accuracy of Computer Aided Detection (CAD4TB) software on chest Xray in screening for pulmonary tuberculosis in comparison with gene-Xpert. Methods: The study was conducted by Radiology Department Lady Reading Hospital Peshawar in affiliation with Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The findings of this study point to a feasible, effective, and even cost-effective strategy for TB screening in a symptomatic group that combines CAD4TB and symptomatology. Earlier research from different contexts are consistent with our findings ( 41 43 ).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this study point to a feasible, effective, and even cost-effective strategy for TB screening in a symptomatic group that combines CAD4TB and symptomatology. Earlier research from different contexts are consistent with our findings ( 41 43 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the screening context, some studies used human CXR interpretation, 19 or varying clinical thresholds to decide who needed to submit a sputum test. 20 , 21 Although most studies did not assess CAD performance in true screening applications, some did. In a formal evidence review of the ‘screening use-case’ undertaken as part of the WHO guidelines process, 12 AUCs ranged from 0.76–0.83 for CAD4TBv6, qXRv2 and Lunitv4.9.0.…”
Section: Diagnostic Performance Of Cad For Tbmentioning
confidence: 99%
“…This confirms the hypothesis that when gastric lavage samples are used on Gene X-pert, there is a lower TB positivity rate in children under 10 years of age at this hospital compared to when X-ray imaging is employed. Similarly, in the study by Nishtar et al (2022), the sensitivity of CAD4TB, a diagnostic tool based on CXR, was reported to be 83.2%, while its specificity was only 12.7%, using GeneXpert as the reference standard.…”
Section: Discussionmentioning
confidence: 82%